P25. Spinal receptive fields are enlarged after trauma but recover in mice. Issue 8 (August 2015) - Hirsch, S.; Ibrahim, A.; Escolano-Lonzano, F.; Schlereth, T.; Birklein, F.
<x xml:space="preserve">Abstract</x> The neurophysiological mechanisms involved in Complex Regional Pain Syndrome (CRPS) are not fully elucidated. The disease can develop after physical limb trauma and persist in humans for many years as a painful and often disabling condition. The acute phase of CRPS with signs of inflammation and beginning centralization of pain can be studied in mice after tibial fracture. In the rodent most of the symptoms do recover within several weeks. To examine neuroplastic changes in the spinal cord accompanying the behavioral symptoms in the mouse CRPS-model we conducted extracellular recordings of WDR neurons in the mouse dorsal horn of the lumbar spinal cord with receptive fields in the paw of the injured versus non-injured leg. Four weeks after tibial fracture, spinal receptive fields were enlarged on the injured side. 12 weeks after the trauma, receptive field sizes recovered. Thus, on the basal central level of the neuronal network in the spinal cord we see a drastic reorganization of the connectivity shortly after limb trauma that subsides in mice.